New Challenges in Offshore Geotechnical Engineering Developments - Pan Hu; Dong-Sheng Jeng (Journal of Marine Science and Engineering)
The exploration and utilisation of marine resources and renewable energy have surged in recent years, driving the need for innovative and resilient solutions [...]